Implementasi Kecerdasan Buatan (Artificial Intelligence) pada Media Pembelajaran Interaktif untuk Meningkatkan Literasi Digital Siswa di SMAN 2 Kota Sungai Penuh - Abelza Pernanda; Hetty Rohayani; Helmina Helmina (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of information technology demands that education effectively integrate digital technology to improve students' digital literacy. However, technology utilization in schools tends to be limited to basic uses and is not yet optimal in supporting interactive learning. Therefore, a Field Work Practice (PKL) activity for Informatics students was conducted at SMAN 2 Kota Sungai Penuh, focusing on the application of Artificial Intelligence (AI) technology in interactive learning media. This research used a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The technology implementation involved the use of various AI-based tools, such as ChatGPT for developing materials and questions, Canva AI for designing interactive presentations, and Quizizz and Google Forms for automated digital evaluations. Students acted as technology facilitators, digital learning media developers, and student practice assistants in the computer lab. The results showed that the application of AI improved learning effectiveness, student engagement, and technical skills in using computers and digital applications. Students became more active, understood the productive use of technology, and developed an awareness of digital ethics and security. Thus, the application of Artificial Intelligence technology in learning provides a real contribution to improving students' digital literacy while also being a form of implementing Informatics science in the educational environment.